Answer:
b=16
Step-by-step explanation:
1) Divide 3 on both sides.
2) 3 divided by 3 and 48 divided 3.
3) Now you're left with 16, so the value of b is 16.
![( {x}^{2} -2x + 3)(x + 1) \\ {x}^{3} - 2 {x}^{2} + 3x + {x}^{2} - 2x + 3 \\ {x}^{3} - {x}^{2} + x + 3](https://tex.z-dn.net/?f=%28%20%7Bx%7D%5E%7B2%7D%20%20-2x%20%2B%203%29%28x%20%2B%201%29%20%5C%5C%20%20%7Bx%7D%5E%7B3%7D%20%20-%202%20%7Bx%7D%5E%7B2%7D%20%20%2B%203x%20%2B%20%20%7Bx%7D%5E%7B2%7D%20%20-%202x%20%2B%203%20%5C%5C%20%20%7Bx%7D%5E%7B3%7D%20%20-%20%20%7Bx%7D%5E%7B2%7D%20%20%2B%20x%20%2B%203)
Therefore, the answer is the first choice.
Answer:
<h3>Solutions are x=2 and x=−2 . At these points the function has vertical asymptotes. To address the range, let's first transform...</h3>
Answer:
![-26,-24,-22](https://tex.z-dn.net/?f=-26%2C-24%2C-22)
Step-by-step explanation:
<em><u>The correct question is</u></em>
The sum of three consecutive even integers is -72. what are the three numbers
Let
x ----> the first consecutive even integer
x+2 ----> the second consecutive even integer
x+4 ----> the third consecutive even integer
we know that
![x+(x+2)+(x+4)=-72](https://tex.z-dn.net/?f=x%2B%28x%2B2%29%2B%28x%2B4%29%3D-72)
solve for x
![3x+6=-72\\3x=-78\\x=-26](https://tex.z-dn.net/?f=3x%2B6%3D-72%5C%5C3x%3D-78%5C%5Cx%3D-26)
so
![x+2=-26+2=-24](https://tex.z-dn.net/?f=x%2B2%3D-26%2B2%3D-24)
![x+4=-26+4=-22](https://tex.z-dn.net/?f=x%2B4%3D-26%2B4%3D-22)
therefore
the numbers are
![-26,-24,-22](https://tex.z-dn.net/?f=-26%2C-24%2C-22)